2022
DOI: 10.1177/01708406221123373
|View full text |Cite
|
Sign up to set email alerts
|

Smartocracy: Context entanglement of the smart city idea and bureaucracy in Russia

Abstract: This paper explores how the smart city idea unfolds in the bureaucratic context. Applying a qualitative approach and the Scandinavian stream of translation theory, we investigate the case of cities’ ‘smartification’ in Russia during 2017–2020. Tracking mechanisms and outcomes of translation, we see the encounter of the smart city idea and bureaucracy as context entanglement, with smartocracy as an epilogue. Context entanglement refers to the mutual co-translation of the smart city idea and bureaucracy by means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…As formalization leaves little room for uncertainty in governance arrangements and contractual agreements, actors increasingly adhere to their own institutional logics, thereby dramatically reducing the solution space and the associated innovation potential. Here our findings on formalization and innovation for smart city development connect to current debates on how city organizing and bureaucracy may influence smart city implementation in view of the translation of complex or external ideas (Khodachek, Aleksandrov, Nazarova, Grossi, & Bourmistrov, 2023).…”
Section: Discussionsupporting
confidence: 81%
“…As formalization leaves little room for uncertainty in governance arrangements and contractual agreements, actors increasingly adhere to their own institutional logics, thereby dramatically reducing the solution space and the associated innovation potential. Here our findings on formalization and innovation for smart city development connect to current debates on how city organizing and bureaucracy may influence smart city implementation in view of the translation of complex or external ideas (Khodachek, Aleksandrov, Nazarova, Grossi, & Bourmistrov, 2023).…”
Section: Discussionsupporting
confidence: 81%
“…later significantly shaped by cross-functional teams’ were observed in seven European cities (Lekkas & Souitaris, 2023, p. 1653). Likewise, in a case study of Russian cities, the organisation progressed from a formal core, through a ‘shadow culture’ stage, and to a final stage characterised by standardisation (Khodachek, Aleksandrov, Nazarova, Grossi, & Bourmistrov, 2023, p. 1640). While these studies have confirmed similar trajectories of organisation, our contribution lies in the different ways in which ecosystem capabilities were aggregated across levels during smart city development.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of Khodachek et al (2023) and Lekkas and Souitaris (2023) have important implications for organization studies. One notable contribution is the recognition that bureaucracy and smart city development are not necessarily conflicting forces but can complement each other (Byrkjeflot & du Gay, 2012).…”
Section: Smart City Studies and Organization Studies: Research At The...mentioning
confidence: 95%
“…Specifically, Khodachek et al (2023) introduce the concept of context entanglement that binds the smart city concept and bureaucracy. They argue that the complexity of the smart city concept necessitates the involvement of bureaucracy as a translating machine capable of dealing with the intricate governance dimensions that characterize smart city efforts.…”
Section: Temporal Structuring Of Organizational Arrangementsmentioning
confidence: 99%
See 1 more Smart Citation